Bortezomib consolidation or maintenance following immunochemotherapy and autologous stem cell transplantation for mantle cell lymphoma: CALGB/Alliance 50403. Issue 6 (6th April 2020) - Kaplan, Lawrence D.; Maurer, Matthew J.; Stock, Wendy; Bartlett, Nancy L.; Fulton, Noreen; Pettinger, Adam; Byrd, John C.; Blum, Kristie A.; LaCasce, Ann S.; Hsi, Eric D.; Liu, Yi Tian; Scott, David W.; et al.
Abstract: Immunochemotherapy followed by autologous transplant (ASCT) in CALGB/Alliance 59909 achieved a median progression‐free survival (PFS) in mantle cell lymphoma (MCL) of 5 years, but late recurrences occurred. We evaluated tolerability and efficacy of adding post‐transplant bortezomib consolidation (BC) or maintenance (BM) to this regimen in CALGB/Alliance 50403, a randomized phase II trial. Following augmented‐dose R‐CHOP/ methotrexate, high‐dose cytarabine‐based stem cell mobilization, cyclophosphamide/carmustine/etoposide (CBV) autotransplant, and rituximab, patients were randomized to BC (1.3 mg/m 2 IV days 1, 4, 8, 11 of a 3‐week cycle for four cycles) or BM (1.6 mg/m 2 IV once weekly × 4 every 8 weeks for 18 months) beginning day 90. The primary endpoint was PFS, measured from randomization for each arm. Proliferation signature, Ki67, and postinduction minimal residual disease (MRD) in bone marrow were assessed. Of 151 patients enrolled; 118 (80%) underwent ASCT, and 102 (68%) were randomized. Both arms met the primary endpoint, with median PFS significantly greater than 4 years ( P < .001). The 8‐year PFS estimates in the BC and BM arms were 54.1% (95% CI 40.9%‐71.5%) and 64.4% (95% 51.8%‐79.0%), respectively. Progression‐free survival was significantly longer for transplanted patients on 50403 compared with those on 59909. Both the PFS and OS were significantly better for those who were MRD‐negative post‐induction. The high risk proliferation signature was associated with adverse outcome. Both BM and BC were efficacious and tolerable, although toxicity was significant. The comparison between studies 50403 and 59909 with long‐term follow up suggests a PFS benefit from the addition of BC or BM post‐ transplant.